A 'fertile soil' for sustainability-related community initiatives: A new analytical framework. (October 2017) - Sekulova, Filka; Anguelovski, Isabelle; Argüelles, Lucia; Conill, Joana
One of the unique and emerging responses to the current ecological, social, political and economic crises has been the emergence of community initiatives in a range of formulas and geographical contexts. We explore their emergence and evolution beyond the analysis of a single fixed set of factors that are expected to contribute to their initiation and growth. Upon reviewing the trajectories of various initiatives in the region of Barcelona (Spain), we argue that the metaphor of the fertile soil provides a useful framework to describe or explain the messy process of emergence and evolution of grassroots and community projects. Fertile soil is understood here as a particular quality of the social texture, characterized by richness, diversity, unknowns but also – by multiple tensions and contradictions. Yet it is not only the diversity of factors but the quality of their mutual relatedness that 'makes' the soil fertile for the emergence of new groups and the continuation of existing ones. Importantly, the seemingly messy social base in which community initiatives emerge is nourished by their inner and outer contradictions. Likewise, the space opened by dealing with conflicting rationalities creates the conditions for new and more resilient strategies and structures to emerge. As community initiatives get established, the 'fertile dilemmas' they frequently face become a key driver of their evolutionary context, contributing to the emergence of new social imaginaries and ways of producing social change.